Marching to Different Drum Beats: A Temporal Perspective on Coordinating Occupational Work - Oborn, Eivor; Barrett, Michael (Organization Science, 2021)
In this paper, we contribute a temporal perspective on work coordination across collaborating occupations. Drawing on an ethnographic study of medical specialists—surgeons, pathologists, oncologists, and radiologists—we examine how their temporal orientations are shaped through the temporal structuring of occupational work. Our findings show that temporal structuring of occupational practices develop in relation to the contingencies and materialities of their work and that this shapes and is shaped by specialists’ temporal orientations. Further, we show that differences in occupations’ temporal orientations have important implications for coordinating work. More specifically, our study reveals how the domination of one temporal orientation can lead to recurrent strain, promoting a competitive trade-off between the different temporal orientations in guiding interaction. This temporal orientation domination is accompanied by a persistent emotional strain and potential conflict. Finally, we suggest that, alternatively, different temporal orientations can be resourced in solving coordination challenges through three interrelated mechanisms, namely juxtaposing, temporal working, and mutual adjusting. In so doing, we show how temporal resourcing can be productive in coordinating work.